Phosphatidylinositide 3-Kinase Contributes to the Anti-Inflammatory Effect of Abutilon crispum L. Medik Methanol Extract. (26th November 2018) - Hunto, Stephanie Triseptya; Shin, Kon Kuk; Kim, Han Gyung; Park, Sang Hee; Oh, Junsang; Sung, Gi-Ho; Hossain, Mohammad Amjad; Rho, Ho Sik; Lee, Jongsung; Kim, Jong-Hoon; Cho, Jae Youl
Abstract : Abutilon crispum L. Medik, better known as bladdermallow, is used as a traditional remedy in India, for its anti-inflammatory effect due to its high content of flavonoids. However, research about its anti-inflammatory effect at the molecular level has not been performed. In this study, we aimed to investigate the mechanism of Abutilon crispum methanol extract (Ac-ME) in inhibiting the inflammatory response by conducting several experiments including cellular and molecular assays. Ac-ME inhibited the production of nitric oxide (NO) in RAW264.7 cells during treatment of LPS and Pam3CSK4 without exhibiting cytotoxicity. Ac-ME also suppressed the mRNA expression of inducible nitric oxide (iNOS) and proinflammatory cytokines such as interleukin (IL)-1 β and IL-6. Moreover, Ac-ME was shown to inhibit the NF- κ B pathway, according to the luciferase reporter gene assay performed with a NF- κ B-Luc construct containing NF- κ B-binding promoter regions under MyD88 and TRIF overexpression conditions, and immunoblotting analysis by determining the phospho-form levels of I κ B α, IKK α / β, and p85, a regulatory domain of phosphatidylinositide 3-kinase (PI3K). Finally, we observed that the level of phospho-p85 induced by the overexpression of spleen tyrosine kinase (Syk) and Src was decreased by Ac-ME at 200  μ g/ml. Therefore, these results suggest that Ac-ME has an anti-inflammatory effect by targeting PI3K in the NF- κ B signaling pathway.